2021
DOI: 10.1007/s10456-020-09766-2
|View full text |Cite|
|
Sign up to set email alerts
|

A novel lymphatic pattern promotes metastasis of cervical cancer in a hypoxic tumour-associated macrophage-dependent manner

Abstract: Lymphatic remodelling in the hypoxic tumour microenvironment (TME) is critically involved in the metastasis of cervical squamous cell carcinoma (CSCC); however, its underlying mechanisms remain unclear. Here, we uncovered a novel lymphatic pattern in the hypoxic TME, wherein lymphatic vessels (LVs) are encapsulated by tumour-associated macrophages (TAMs) to form an interconnected network. We describe these aggregates as LVEM (LVs encapsulated by TAMs) considering their advantageous metastatic capacity and acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 55 publications
(64 reference statements)
0
28
0
Order By: Relevance
“…Recent evidence has indicted that IL‐6 secreted by tumour‐associated macrophages enhances metastatic colonisation of CRC cells (Toyoshima et al., 2019; Zhong et al., 2020). Similarly, CCL1 and CCL2 have been shown to promote tumour metastasis by facilitating tumour‐associated macrophage recruitment (Chen et al., 2018, 2021). These data support our findings that CRC‐EV‐activated macrophages release IL‐6, CCL1 and CCL2 to potentiate CRC cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has indicted that IL‐6 secreted by tumour‐associated macrophages enhances metastatic colonisation of CRC cells (Toyoshima et al., 2019; Zhong et al., 2020). Similarly, CCL1 and CCL2 have been shown to promote tumour metastasis by facilitating tumour‐associated macrophage recruitment (Chen et al., 2018, 2021). These data support our findings that CRC‐EV‐activated macrophages release IL‐6, CCL1 and CCL2 to potentiate CRC cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…In GO enrichment analysis, cell division-related biological processes such as nucleosome assembly, nucleosome organization, chromatin assembly, or disassembly were found to be deeply involved in the initial lymphatic metastasis of COAD. This might be due to increased cancer cell division and the proliferation of new lymphatic vessels [ 40 , 41 ]. KEGG enrichment analysis revealed that systemic lupus erythematosus was the most significantly enriched pathway, and furthermore, the single GSEA validated this result, suggesting that the systemic lupus erythematosus pathway may be crucial for initial lymphatic metastasis in COAD.…”
Section: Discussionmentioning
confidence: 99%
“…IHC staining of human cervical squamous cell carcinoma tissue demonstrated that, under hypoxic conditions, lymphatic vessels were encapsulated by CD163 + TAMs, and the LVD was higher compared with that under normoxic conditions (108). These structures were referred to as lymphatic vessels encapsulated by TAMs (LVEM) (108). Hypoxic TAMs exhibited high IL-10 expression (108).…”
Section: Tams Induce Lymphangiogenesismentioning
confidence: 99%